(untitled) (Orfeu, 2025)
Illustrating the pedagogical actings of Willy Corrêa de Oliveira in two moments of his career as a teacher –in his work at the School of Communication and Arts at the University of São Paulo, and after his retirement –, this text discusses the difficulties inherent in teaching composition today, as faced by Willy at these two points, given the lack of a common language shared in classical music in our time. A point of greatest interest, then, is the presentation of the pedagogical strategy proposed by the professor in his Twelve-tone Composition Course (unpublished, completed in 2022). As materials and methodology, we use the composer’s written essays and interviews provided by him to the authors, from which it is possible to extract the pedagogical guidelines that surround the object of study. The work, in its current stage, concludes that Oliveira’s Twelve-tone Composition Course has, in its elaboration plan, the potential to guide students through the process of learning musical composition considering a vision of the practice of classical music today, based on the search for creation, to the detriment of the repetition of models from the past. liveira in these two moments. A point of greatest interest, then, is the presentation of the pedagogical strategy proposed by the professor in his Twelve-tone Composition Course (unpublished, completed in 2022). As materials and methodology, we use the composer’s written essays and interviews provided by him to the authors, from which it is possible to extract the pedagogical guidelines that surround the object of study. The work, in its current stage, concludes that Oliveira’s Twelve-tone Composition Course has, in its elaboration plan, the potential to lead students to the mastery of musical composition considering the inherent needs to the practice of creating classical music today.